Comparable Estimates of Returns to Schooling Around the World - Montenegro, Claudio E.; Patrinos, Harry Anthony (World Bank Group, Washington, DC, 2014)
Rates of return to investments in schooling have been estimated since the late 1950s. In the 60-plus year history of such estimates, there have been several attempts to synthesize the empirical results to ascertain patterns. This paper presents comparable estimates, as well as a database, that use the same specification, estimation procedure, and similar data for 139 economies and 819 harmonized household surveys. This effort to compile comparable estimates holds constant the definition of the dependent variable, the set of control variables, the sample definition, and the estimation method for all surveys in the sample. The results of this study show that (1) the returns to schooling are more concentrated around their respective means than previously thought; (2) the basic Mincerian model used is more stable than may have been expected; (3) the returns to schooling are higher for women than for men; (4) returns to schooling and labor market experience are strongly and positively associated; (5) there is a decreasing pattern over time; and (6) the returns to tertiary education are highest.